Emotional Intelligence and Teacher Productivity and Performance in Public Elementary Schools: An Input for a School-Based Intervention Program - Haide J. Galang; Alberto D. Yazon; Marcial Bandoy; Lerma P. Buenvenida; Karen A. Manaig (Research Synergy Foundation, 2024)
Emotional intelligence (EI) is crucial to every individual's well-being. It is a significant factor in establishing positive relationships, especially in the post-pandemic era. Teachers play vital roles in education as they are the front liners who directly interact with learners, parents, and stakeholders. Therefore, they should have a strong EI to employ constructive approaches in managing their school environment. Therefore, educational leaders and school administrators must recognize how personal challenges impact teachers' emotional intelligence, particularly during the pandemic, by establishing reliable support mechanisms that foster a positive learning atmosphere. These resources can help teachers manage personal issues and empower them to support their students effectively. The study analyzed the impact of Emotional Intelligence on teachers’ productivity and performance as input for a school-based intervention program. This descriptive research utilized a quantitative correlation approach. A simple random sampling technique was employed to determine the population sample size. The questionnaire was sent to 655 target respondents from two sub-offices of the Division of Laguna, Department of Education, Philippines, through two methods: via a Google link or using paper and pen, with the permission of their school heads. The questionnaire was sent to the target participants in two ways: through a Google link or through paper-and-pen with the permission of the participants’ school heads. The results revealed that the respondents demonstrated high emotional intelligence but average stress management. On the other hand, they were both at high levels in terms of productivity and performance. The relationship between emotional intelligence and teachers’ productivity exhibited moderate correlations, while there was a strong correlation between Emotional Intelligence and Teaching Performance. Finally, some demographic factors influenced the relationship between emotional intelligence (EI) and Teaching Performance. Most school interventions focus on skill development, curriculum development, teaching methodologies, or student support systems, and Emotional Intelligence is often neglected. Providing emotional support to teachers is important for recognizing how their emotional states impact their effectiveness and the learning environment. This support can help to continually enhance productivity and performance, leading to better learning outcomes.